Teaching Multilingual and Multicultural Children in Finnish Early Childhood Education and Care (ECEC) - Sorhent, Lavinia (My University, 2025)
This thesis provides insight into the teaching practices of both pre-service and in-service ECEC teachers who engage with multilingual and multicultural children in early childhood and care settings in Finland. Additionally, it investigates how teacher attitudes shape the educational experiences of multilingual and multicultural children in Finnish ECEC, focusing on creating an inclusive learning environment for every young learner. This study conducts a thorough literature review to examine how teachers’ perceptions and actions influence pedagogical practices, highlighting the extent of culturally responsive education in ECEC. Utilising the attribution theory, the intercultural competence frameworks, and Vygotsky’s sociocultural theory, the research analyses the effects of teacher attitudes on the learning of multilingual and multicultural children. The findings reveal that while Finnish educational policies promote linguistic and cultural inclusivity, their practical application varies. Whereas ECEC teachers acknowledge the advantages of multilingualism, educators face challenges in implementing inclusive teaching strategies due to monolingual training and institutional barriers. This research underscores the necessity for targeted professional development, policy revisions, and enhanced teacher training programs to appreciate multilingualism and multiculturalism, ultimately fostering a more inclusive ECEC system.
Keywords: Early Childhood Education and Care (ECEC), teacher attitudes, multilingual, multicultural learners